Irish Cepaea nemoralis land snails have a cryptic Franco-Iberian origin that is most easily explained by the movements of mesolithic humans - Grindon, Adele J.; Davison, Angus (Public Library of Science, 2013)
The origins of flora and fauna that are only found in Ireland and Iberia, but which are absent from intervening countries, is one of the enduring questions of biogeography. As Southern French, Iberian and Irish populations of the land snail Cepaea nemoralis sometimes have a similar shell character, we used mitochondrial phylogenies to begin to understand if there is a shared “Lusitanian” history. Although much of Europe contains snails with A and D lineages, by far the majority of Irish individuals have a lineage, C, that in mainland Europe was only found in a restricted region of the Eastern Pyrenees. A past extinction of lineage C in the rest of Europe cannot be ruled out, but as there is a more than 8000 year continuous record of Cepaea fossils in Ireland, the species has long been a food source in the Pyrenees, and the Garonne river that flanks the Pyrenees is an ancient human route to the Atlantic, then we suggest that the unusual distribution of the C lineage is most easily explained by the movements of Mesolithic humans. If other Irish species have a similarly cryptic Lusitanian element, then this raises the possibility of a more widespread and significant pattern.